Atheism and Atheists: Western and Islamic perspective - Abdul Razak, Nur Afifah; Mohd Amin, Wan Mohd Azam (IIUM Press, 2021)
This article aims to study the primary and secondary definition of atheism and theists according to the Western and Islamic Perspectives. This research will highlight some of the typologies of atheists, sociological and psychological conditions of atheist and self-identified atheists in modern ideologies. A further discussion and exploration will also cover the response of Muslim scholars and philosophers to atheism and atheists such as Al-Ghāzāli and Saʿīd Ramaḍān Al-Butiy. This study employs a qualitative method by analysing related books, dictionaries, encyclopaedias, and journal articles.The finding indicates that there are insufficient sources in defining the word atheism in Islam as compared to the Western connotations.